Psychological Adjustment as an indicator of Mental Health: El Ajuste Psicológico como indicador de Salud Mental - Matos-Ramírez, Patricia (2024)
Psychological adjustment is fundamentally conceptualized as the balance, interaction or dynamic and dialectical adaptation that each individual maintains with his environment, for which an intrapsychic dimension (biopsychological) and an interpsychic dimension (psychosocial) are taken into account, ruled by principles and laws of learning; this balance is seen in behavior which is psychosocial in nature. Method: Literature review study. Journals were consulted from the following databases: American Psychological Association, SCOPUS, SciELO and Google Scholar. Result: The review of documents whose common name is psychological adjustment, allows us to recognize the following associated variables such as anxiety, depression, psychological well-being, and personality.Conclusion: The term psychological adjustment refers to a profile of indicators associated with the mental health of an individual.